Q: 5 times negative 1 squared minus 3 times 3 times 5?

Write your answer...

Seven minus negative two times negative 4 is equal to -1

(5w + 1)(w + 1)

Two plus 3 minus 2 times 1 squared plus 4 times 16 squared minus 4 times 2 is equal to 1,019.

no

Negative 2 ☻ed is -4 and -4 - 5= -1. ♥

1

-((x + 8)(x - 1))

You have to put your heart into it!

Minus 1.

-7

No, unless "a" happens to be equal to 0, or to 1.

3c(squared)-17c-6 = 0 (3c+1)(c-6) = 0 c= negative one third or positive 6

sin squared

it equals positive one. one squared is always one. if they're both negative, negative times negative is always positive.

-1² = 1

Negative plus a negative is a negative. Ex. -1+-1=-2 Negative times a negative is a positive. -2*-2=4 But a negative [minus] plus a positive [plus] can be minus, zero or plus: For example, -3 + 2 = -1 -3 + 3 = 0 -3 + 4 = +1

When you multiply a negative number by a positive number then the product is always negative. When you multiply a positive number by a negative number then the product is always negative. ( - 2 ) ( + 3 ) = - 6 ( - 4 ) ( 1 ) = - 4 ( - 1 ) 2 = - 2 ( + 2 ) ( - 2 ) = - 4 ( 3 ) ( - 2 ) = - 6 4 ( - 2 ) = - 8

(-3)-(4)=(-3)+4=1 Minus times minus equals plus. The reason for this we need not discuss.

negative 2 over 6

Multiply both sides by sin(1-cos) and you lose the denominators and get (sin squared) minus 1+cos times 1-cos. Then multiply out (i.e. expand) 1+cos times 1-cos, which will of course give the difference of two squares: 1 - (cos squared). (because the cross terms cancel out.) (This is diff of 2 squares because 1 is the square of 1.) And so you get (sin squared) - (1 - (cos squared)) = (sin squared) + (cos squared) - 1. Then from basic trig we know that (sin squared) + (cos squared) = 1, so this is 0.

A negative minus a positive is a negative. i.e -1-(+1)= -2

-1 minus -6 is 5

This is because anything squared is always positive. For example: 1 times 1= 1 and (-1) times (-1)= 1. The only number that when squared will give you a negative number are irrational, such as i. i is equal to the square root of (-1).

2x squared minus 5x minus 3 factored is (2x+1)(x-3).

xcubed-1 Answer::(X-1)(Xsquared+X+1) when you factor xcubed minus a number its the same thing as x cubed minus y cubed and x cubed minus y cubed factors to:: (x-y)(xsquared+xy+y squared) the first factor, (x-y), is the cubed root of the first and the cubed root of the second, so in the answer i have (x-1), which is x cubed minus one cubed :) the second factor, (xsquared+xy+ysquared), you take the first number squared, Xsquared, then the first and second one multiplied together, XY, and then the second number squared, Ysquared, so in the answer i have (xsquared+x+1), which is x squared, then x times 1 which is just x, and positive 1, which is negative 1 squared :) x^3 - 1